APPLICATION OF THE STAD TYPE COOPERATIVE MODEL ASSISTED BY PRACTICE TO IMPROVE STUDENTS LEARNING OUTCOMES - Sariyyah, Nining; Bia, Maria Varina; Waru, Maria Irmania (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This study aims to improve science learning outcomes in grade IV students of Gmit Ende 4 Elementary School. This type of research is classroom action research (CAR). The subjects of the study were grade IV students of Gmit Ende 4 Elementary School with a total of 20 students. Data were collected using test techniques, observations, field notes, and documentation. The data were then analyzed by comparing the results of the pre-test with the post-test of student learning completeness after the implementation of the action in cycle I. The results showed that before the action only (15%) students achieved the minimum completeness criteria (KKM). After the implementation of the action in cycle I, student learning completeness increased (100%). This increase shows that the STAD type Cooperative learning model assisted by practicum can improve student learning outcomes.